Examining the role of relative age on leadership behaviours among female ice hockey players: An exploratory investigation - Chittle, L.; Horton, S.; Dixon, J. C. (Journal of Amateur Sport, 2020)
The aim of this study was to examine the influence of relative age on self-reported leadership behaviors among competitive female ice hockey players. Secondary purposes included examining whether a relative age effect (RAE) was present within the sample and if leadership behaviors differed according to leader status (i.e., formal versus informal leaders). Canadian female ice hockey players (ages 15-18 years) completed an online survey that contained the Leadership Scale for Sport along with additional demographic questions. Players were segmented into birth quartiles based upon Hockey Canada`s selection date and classified by leadership status. The MANOVA suggested that the frequency of leadership behaviors displayed by these athletes did not differ across birth quartiles. Furthermore, although there was a RAE trend within this sample of competitive female ice hockey players, the differences relative to population distributions were not statistically significant. Finally, formal leaders (i.e., captains/alternate captains) reported higher levels of social support, positive feedback, democratic behavior, and training and instruction than informal leaders. It appears that relative age is not a discriminating factor with respect to leadership behaviors. Competitive female ice hockey may be an avenue for all players, regardless of their date of birth, to develop and demonstrate leadership.